The protective role of 3-Indoleglyoxylic acid in Bisphenol S-induced intestinal barrier dysfunction via mitochondrial ROS-Mediated IL-17/CXCL10/TNF-α signaling - Jing Wang; Guolei Niu; Huanzhuo Mai; Xianan Zhang; Jiahao Zhu; Bin Li; Yushuang Gao; Tengkai Huang; Qingtao Meng; Rui Chen (Environment International)
Bisphenol S (BPS) has become extensively used in the manufacturing of consumer products. BPS mainly enters the body through food and water, with oral exposure targeting the gastrointestinal tract. However, its safety profile remains contentious and warrants further investigation. In this study, we aimed to assess whether BPS exerts harmful effects on the body in the absence of overt pathological damage. Our results revealed that although BPS did not lead to significant histopathological damage, it induced intestinal barrier dysfunction. Additionally, in vitro investigations utilizing NCM460 cells and human-derived colorectal organoids demonstrated that BPS exposure induced mitochondrial reactive oxygen species (ROS) levels in intestinal endocrine cells (EECs), upregulating the expression of inflammatory mediators TNF-α and CXCL10. Using a DSS-induced colitis mouse model, it was found that BPS exposure exacerbates the progression of intestinal inflammatory diseases. Analysis of single-cell databases demonstrated a significant reduction in the expression of CHGA, a functional protein of enteroendocrine cells (EECs), in patients with inflammatory bowel disease (IBD). The expression of CHGA showed a significant negative correlation with the expression of IL17. Notably, supplementation with 3-Indoleglyoxylic acid effectively mitigates the intestinal damage induced by BPS. These findings highlight the role of mitochondrial oxidative stress and IL-17/CXCL10/TNF-α signaling in BPS-induced intestinal damage and demonstrate the therapeutic potential of 3-Indoleglyoxylic acid in mitigating these effects.